A Composite Lactide-Mineral 3D-Printed Scaffold for Bone Repair and Regeneration - Fairag, Rayan; Li, Li; Ramirez-GarciaLuna, Jose Luis; Taylor, M. Scott; Gaerke, Brian; Weber, Michael H.; Rosenzweig, Derek H.; Haglund, Lisbet (Frontiers in Cell and Developmental Biology, 2021)
Orthopedic tumor resection, trauma or degenerative disease surgeries can result in large bone defects and often require bone grafting. However, standard autologous bone grafting has been associated with donor site morbidity and/or limited quantity. As an alternate, allografts with or without metallic or polyether-etherketone have been used grafting substitutes. However, these may have drawbacks as well, including stress shielding, pseudarthrosis, disease-transmission and infection. There is therefore a need for alternative bone substitutes, such as the use of mechanically compliant three-dimensional (3D)-printed scaffolds. Several off-the-shelf materials are available for low-cost fused deposition 3D printing such as polylactic acid (PLA) and polycaprolactone (PCL). We have previously described the feasibility of 3D-printed PLA scaffolds to support cell activity and extracellular matrix deposition. In this study, we investigate two medical-grade filaments consistent with specifications found in American Society for Testing and Materials (ASTM) standard for semi-crystalline polylactide polymers for surgical implants, a pure polymer (100M) and a copolymeric material (7415) for their cytocompatibility and suitability in bone tissue engineering. Moreover, we assessed the impact on osteo-inductive properties with the addition of β-TCP minerals and assessed their mechanical properties. 100M and 7415 scaffolds with the additive β-TCP demonstrated superior mesenchymal stem cells (MSC) differentiation detected via increased alkaline phosphatase activity (6-fold and 1.5-fold, respectively) and mineralized matrix deposition (14-fold and 5-fold, respectively) in vitro. Furthermore, we evaluated in vivo compatibility, biosafety and bone repair potential in a rat femur window defect model. 100M+ β-TCP implants displayed a positive biosafety profile and showed significantly enhanced new bone formation compared to 100M implants evidenced by µCT (39% versus 25% bone volume/tissue volume ratio) and histological analysis 6 weeks post-implantation. These scaffolds are encouraging composite biomaterials for repairing bone applications with a great potential for clinical translation. Further analyses are required with appropriate evaluation in a larger critical-sized defect animal model with long-term follow up.